A randomized multicentre trial to compare revascularization with optimal medical therapy for the treatment of chronic total coronary occlusions. (2nd May 2018) - Werner, Gerald S; Martin-Yuste, Victoria; Hildick-Smith, David; Boudou, Nicolas; Sianos, Georgios; Gelev, Valery; Rumoroso, Jose Ramon; Erglis, Andrejs; Christiansen, Evald Høj; Escaned, Javier; di Mario, Carlo; Hovasse, Thomas; et al.
Abstract: Aims: The clinical value of percutaneous coronary intervention (PCI) for chronic coronary total occlusions (CTOs) is not established by randomized trials. This study should compare the benefit of PCI vs. optimal medical therapy (OMT) on the health status in patients with at least one CTO. Method and results: Three hundred and ninety-six patients were enrolled in a prospective randomized, multicentre, open-label, and controlled clinical trial to compare the treatment by PCI with OMT with a 2:1 randomization ratio. The primary endpoint was the change in health status assessed by the Seattle angina questionnaire (SAQ) between baseline and 12 months follow-up. Fifty-two percent of patients have multi-vessel disease in whom all significant non-occlusive lesions were treated before randomization. An intention-to-treat analysis was performed including 13.4% failed procedures in the PCI group and 7.3% cross-overs in the OMT group. At 12 months, a greater improvement of SAQ subscales was observed with PCI as compared with OMT for angina frequency [5.23, 95% confidence interval (CI) 1.75; 8.71; P  = 0.003], and quality of life (6.62, 95% CI 1.78–11.46; P  = 0.007), reaching the prespecified significance level of 0.01 for the primary endpoint. Physical limitation ( P  = 0.02) was also improved in the PCI group. Complete freedom from angina was more frequent with PCI 71.6% than OMT 57.8% ( P  = 0.008). There was no periprocedural death or myocardial infarction. At 12 months, major adverse cardiac events were comparable between the two groups. Conclusion: Percutaneous coronary intervention leads to a significant improvement of the health status in patients with stable angina and a CTO as compared with OMT alone. Trial registration: NCT01760083.